Comparação da ultrassonografia e da tomografia computadorizada em pacientes com suspeita de apendicite aguda - El Hassan, Samira (2014)
Introduction: Acute appendicitis is the process of the inflamation of the appendix and it is the most frequent cause of acute abdomen. About 50% of patients with acute appendicitis show classic clinical findings. The others have atypical manisfestations which make diagnosis more difficult, such as in pregnant women, women of childbearing age, and patients younger than ten and more than fifty years of age. At the time of surgery, approximately 35% of the cases are in the advanced phase with perforation and local abscesses. Methods of diagnosis such as ultrasonography and computed tomography can help in the diagnosis of acute appendicitis minimizing surgical delay and reducing appendix perforation and unnecesarry appendectomies. Patients with typical signs and symptoms of acute appendicitis should be assessed and undergo appendectomy. Those with atypical presentation should have image exams. First, they should have an ultrasonography. If the exam doesn't present clearly or if it isn't conclusive, computed tomography should be performed. Objetive: Determine sensitivity and specificity of ultrasonography and computed tomography of patients suspected of having acute appendicitis. Verify a positive diagnosis of acute appendicitis by computed tomography when ultrasonography results are negative in patients suspected of acute appendicitis. Casuistic and method: Prospectively, we analyzed 60 patients, from January of 2006 to May of 2007, between 2 and 90 years old, of both sexes, from the Surgery Department of the Hospital de Base de São Jose do Rio Preto who have been sent to the Radiology Department (Ultrasonography and Tomography Unit) of the above mentioned hospital. The ultrasonography exams were done with a graded compression technique. The computed tomography exams were realized with colonic contrast administered rectally. The conventional axial images of 5 mm of thickness were taken from the pelvic region. Afterwards, iodine contrast was given intravenously and tomographic sections were taken by the helical technique with 5mm of thickness in the pelvic region. After this, other sections of 10mm of thickness were taken of the entire abdomen. Results: Of 60 patients that had ultrasonography, 40 (66.67%) presented positive exams for acute appendicitis. The ultrasonography sensitivity for acute appendicitis was 100%, while the specificity was 83.33%. Of 27 patients that underwent computed tomography, 19 (70.37%) presented negative exams for acute appendicitis. The sensitivity of computed tomography to acute appendicitis was 100%, and the specificity was 33.33%. Conclusion: The diagnosis of acute appendicitis by imaging methods helps to reduce the frequency of unnecessary appendicetomies, frequent complications because of delayed diagnosis, the costs of exams, and long hospital stays.